Dar es Salaam Urban Parks and Green areas Survey - 2016 - Tibesigwa, Bayela (University of Gothenburg, 2021)
The survey is part of a project on Ecosystem Services Accounting for Development (ESAfD) in six different countries: Beijing (China), San José (Costa Rica), Addis Ababa (Ethiopia), Nairobi (Kenya), Cape Town (South Africa), and Dar es Salaam (Tanzania). The surveys were jointly designed. However, local surveys are contingent to local realities. The ESAfD project is jointly executed by the Environment for Development (EfD) initiative and the Swedish Environmental Protection Agency (SEPA), and funded by the Swedish International Development Cooperation Agency (Sida). The objective of the project is to conduct ecosystem services valuation using techniques robust with the System of National Accounts (SNA). By rigorously linking biophysical and socioeconomic data, the results are relevant not only for national accounting but also for local and regional landscape planning.
This submission consists of data from Dar es Salaam Urban Parks and Green areas Survey collected by EfD Tanzania.

The survey is part of a project on Ecosystem Services Accounting for Development (ESAfD) in six different countries: Beijing (China), San José (Costa Rica), Addis Ababa (Ethiopia), Nairobi (Kenya), Cape Town (South Africa), and Dar es Salaam (Tanzania). The surveys were jointly designed. However, local surveys are contingent to local realities. The ESAfD project is jointly executed by the Environment for Development (EfD) initiative and the Swedish Environmental Protection Agency (SEPA), and funded by the Swedish International Development Cooperation Agency (Sida). The objective of the project is to conduct ecosystem services valuation using techniques robust with the System of National Accounts (SNA). By rigorously linking biophysical and socioeconomic data, the results are relevant not only for national accounting but also for local and regional landscape planning.
This submission consists of data from Dar es Salaam Urban Parks and Green areas Survey collected by EfD Tanzania.
Dar es Salaam Urban Parks and Green areas Survey - 2016
Keywords: land cover; land-cover; Land use; Markanvändning; urban amenity; urban amenity; Land use and planning; Markanvändning och planering; Social and Economic Geography; Social och ekonomisk geografi; Environment; Miljö